Development of a new route for Fe-C-Al cast iron production - Shaha, Sugrib Kumar; Dyuti, S.; Haque, Md. Mokammel; Maleque, Md. Abdul (Asian Network for Scientific Information, 2010)
Fe-C-Al alloy system spheroidal graphite cast iron has enormous benefits such as higher strength and hardness, better wear and oxidation resistance etc. at room temperature as well as high temperature. However, its application is not still being popularized due to the production difficulties. In this investigation, a special type of design was developed to perform the magnesium (Mg) treatment in the melt. The raw materials were melted in an induction furnace and later liquid metal was treated using pure Mg foil for spherodization in special crucible. The microstructural study was performed using scanning electron microscope (SEM). The chemical analysis shows a great breakthrough in Mg recovery of Fe-C-Al alloy system spheroidal graphite cast iron. It is also shown that the mechanical properties such as hardness, tensile strength and ductility are comparable to the previous research work.